Safety profiles of vancomycin in pediatrics based on China hospital pharmacovigilance system: A retrospective cohort study - Zhijie Huang; Xiuming Pan; Yao Chen; Weida Chen; Quanyao Chen; Zhiyi Huang; Jiemin Chen; Jianhui Yang; Can Cai (European Journal of Inflammation)
The safety of vancomycin in children requires special attention. The evidence from active pharmacovigilance systems about vancomycin-related adverse drug reactions (ADRs) was rare. We aimed to investigate the association between doses of vancomycin and ADRs among children. This retrospective cohort study included a total of 643 inpatient children. Children who received vancomycin were regarded as exposed groups and classified into low-dose, normal-dose, and high-dose groups. Those who did not receive vancomycin and had similar severity of infection were classified into the unexposed group. ADR signal detection was performed by the China Hospital Pharmacovigilance System. Logistic regression analyses were conducted to explore the effect of intravenous vancomycin on ADRs. This study included 156 patients (178 ADR cases) in the exposed group and 487 patients (364 ADR cases) in the unexposed group. The top three reported ADRs were eosinophilia ( n = 75, 48.1%), hemoglobin decreased ( n = 72, 46.2%), and blood bilirubin increased ( n = 13, 8.3%) in the exposed group. Patients in the low-dose, normal-dose, and high-dose groups showed a higher risk of hemoglobin decreased when compared with those in the unexposed group, with the fully adjusted ORs (95% CIs) of 6.91 (3.61, 13.20), 7.80 (3.87, 15.76), and 8.80 (4.08, 19.01), respectively. Besides, compared with patients in the unexposed group, those in the normal-dose and high-dose groups show a significantly higher risk of eosinophilia and blood bilirubin increased, respectively. It is important to monitor eosinophilia, hemoglobin decreased, and blood bilirubin increased in pediatrics receiving vancomycin, especially those receiving normal-dose and high-dose vancomycin.